2008
DOI: 10.1002/ddrr.25
|View full text |Cite
|
Sign up to set email alerts
|

The cerebellar mutism syndrome and its relation to cerebellar cognitive function and the cerebellar cognitive affective disorder

Abstract: The postoperative cerebellar mutism syndrome (CMS), consisting of diminished speech output, hypotonia, ataxia, and emotional lability, occurs after surgery in up to 25% of patients with medulloblastoma and occasionally after removal of other posterior fossa tumors. Although the mutism is transient, speech rarely normalizes and the syndrome is associated with long-term adverse neurological, cognitive, and psychological sequelae. The clinical, neuroradiographic, and neuropsychological findings associated with CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(72 citation statements)
references
References 63 publications
0
69
0
3
Order By: Relevance
“…Significant correlations are also found between duration of mutism and abnormalities on SPECT scans of the left temporal lobe, the left and right basal nuclei, and the right frontal lobe [50]. Although the mutism is transient, speech rarely normalizes and the syndrome is associated with long-term adverse neurological, cognitive, and psychological sequelae [54]. Palmer et al showed that patients treated for medulloblastoma and suffered with cerebellar mutism, had an increased risk for neurocognitive impairment for over 12 months postoperatively [55].…”
Section: Cerebellar Mutismmentioning
confidence: 94%
“…Significant correlations are also found between duration of mutism and abnormalities on SPECT scans of the left temporal lobe, the left and right basal nuclei, and the right frontal lobe [50]. Although the mutism is transient, speech rarely normalizes and the syndrome is associated with long-term adverse neurological, cognitive, and psychological sequelae [54]. Palmer et al showed that patients treated for medulloblastoma and suffered with cerebellar mutism, had an increased risk for neurocognitive impairment for over 12 months postoperatively [55].…”
Section: Cerebellar Mutismmentioning
confidence: 94%
“…33 Posterior fossa syndrome is a broader term that includes CM and, in addition, movement disorders (ataxia and hypotonia) and a wide spectrum of neurobehavioral abnormalities. 39 Some authors regard CMS as a synonym for posterior fossa syndrome (PFS) and use the terms interchangeably, 55,82,109 while others believe that CM is a severe form of cerebellar dysarthria. 33,44,68,89,99,103,105 In 1998, Schmahmann and Sherman 84 introduced the term cerebellar cognitive affective syndrome to describe a constellation of neuropsychological findings in adult patients with diseases confined to the cerebellum.…”
Section: Definitionsmentioning
confidence: 99%
“…En la literatura se han descrito múltiples factores de riesgo relacionados, dentro de los más citados destacan: compromiso tumoral del tronco cerebral 4,25 , la localización en línea media 26,27 , la incisión del vermis cerebeloso 29 y la histología del tumor. En relación a este último, cabe destacar que el meduloblastoma presenta una mayor incidencia de mutismo cerebeloso postoperatorio 27,28 .…”
Section: Introductionunclassified
“…En el mutismo cerebeloso y en el síndrome de mutismo cerebeloso el sustrato anatómico más citado en la literatura tiene relación con el núcleo dentado y el tracto dento-rubro-talámico [17][18][19][20][21][22][23] .…”
Section: Introductionunclassified